2015
DOI: 10.1111/asj.12473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of calpain and caspase systems activities during ageing of two bovine muscles by degradation patterns of αII spectrin and PARP‐1

Abstract: The activities of calpain and caspase systems during ageing in Longissimus lumborum (LL) and Infraspinatus (IS) muscles of Italian Simmental young bulls (Bos taurus) were assessed. Samples from 10 animals were collected within 20 min of exsanguination (T0), after 48 h (T1) and 7 days (T2) post mortem. Calpain and caspase activity were evaluated based on the formation of αII spectrin cleavage products of 145 kDa (SBDP145) and 120 kDa (SBDP120), respectively. Caspase activity was also assessed by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…As indicated in Figure E, MgIG dose‐dependently up‐regulated cleaved‐caspase‐3/9 without increasing the levels of procaspase‐3/9, suggesting that such caspase activation was involved in MgIG‐induced HSCs apoptosis. Furthermore, the cleaved form of PARP, which was one of the key markers of apoptosis, was increased by MgIG treatment . Caspase activation was consistent with the nuclear morphological changes (Fig.…”
Section: Resultssupporting
confidence: 73%
“…As indicated in Figure E, MgIG dose‐dependently up‐regulated cleaved‐caspase‐3/9 without increasing the levels of procaspase‐3/9, suggesting that such caspase activation was involved in MgIG‐induced HSCs apoptosis. Furthermore, the cleaved form of PARP, which was one of the key markers of apoptosis, was increased by MgIG treatment . Caspase activation was consistent with the nuclear morphological changes (Fig.…”
Section: Resultssupporting
confidence: 73%
“…This lack of difference was expected considering that beef tenderness depends on factors such as breed, age and post mortem pH 36 that were similar between experimental groups. On average, the decrease in WBSF during aging was probably due to post mortem proteolysis …”
Section: Resultsmentioning
confidence: 99%
“…On average, the decrease in WBSF during aging was probably due to post mortem proteolysis. 37 Table 3 reports the fatty acid composition of the intramuscular fat of meats from experimental groups. The differences between experimental groups involved mainly saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA).…”
Section: Animal Performance Carcass and Meat Characteristicsmentioning
confidence: 99%
“…Casp3 and Casp9 are involved in the intrinsic pathway of apoptosis. In spite of their central role in apoptosis, the involvement of caspases in meat tenderisation, by means of proteolytic degradation, is still debated (Sacc a et al 2015a(Sacc a et al , 2015b. In our trial, no significant differences were found between G and SG in the expression of Casp3 and Casp9 mRNA (Table 3), in line with Capn and Cast genes expression.…”
Section: Rna and Protein Expression Of Considered Genesmentioning
confidence: 47%